Novelties for Wedelia (Asteraceae, Heliantheae) in Minas Gerais, Brazil: a new species and a rediscovery after over 70 years - Bueno, Vinícius Resende; Ramos, Renato; Almeida, Maria Luiza Campos De; Hemetrio, Nadja Simbera; Santos, Fabrício Rodrigues Dos; Prado, Jefferson; Zavatin, Danilo Alvarenga (Phytotaxa, 2025)
Even though the high plant species richness of Minas Gerais state (Brazil) is widely known, some areas have historically been underrepresented in botanical collections, such as the north and central-west of Minas Gerais. From these two regions, two unexpected records of Wedelia have emerged: a new species and a rediscovery for the state after 70 years. Firstly, the new species is named here W. riopardensis; it resembles W. diffusiflora by elliptic leaf blade (vs. ovate), abaxial surface villose (vs. strigose), involucre 4-seriate (vs. 3-seriate), and disc florets 8.1–9 mm long (vs. ca. 7 mm). Second, since its type collection, about 70 years ago, W. egleri had never been collected again in Minas Gerais; here we present its rediscovery involving a nomenclatural recombination. Morphological descriptions of the two species are provided, with photo plates, mapped geographic distributions, and conservation status discussed. In addition, a map with the updated Global and Brazilian distribution and species richness of Wedelia species is presented and a taxonomic key to the most misidentified Brazilian genera of Asteraceae with Wedelia (Aldama, Calea, and Dimerostemma) is provided to assist with identification of these groups.